2013
DOI: 10.1093/pasj/65.sp1.s13
|View full text |Cite
|
Sign up to set email alerts
|

Long-Period Oscillations of Sunspots by NoRH and SSRT Observations

Abstract: Long-term oscillations of microwave emission generated in sunspot magnetospheres are detected with the Nobeyama Radioheliograph (NoRH) at a frequency of 17 GHz, and the Siberian Solar Radio Telescope (SSRT) at 5.7 GHz. Significant periodicities in the range of 22-170 min are found in the variation of the emission intensity, polarisation and the degree of circular polarisation. Periods of the oscillations are not stable: they are different in different sunspots and in the same sunspot on different days. A cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Long-period magnetic field oscillations were detected from SOHO/MDI and ground-based data at Pulkovo Observatory by Nagovitsyna and Nagovitsyn (2002), Efremov et al (2007Efremov et al ( , 2009Efremov et al ( , 2012bEfremov et al ( , 2013, Kallunki and Riehokainen (2012), and with NoRH and SSRT instruments by AbramovMaximov et al (2013) and Bakunina et al (2013), finding periods of 30 -40, 70 -100, and 150 -200 and 800 -1300 minutes and amplitudes of about 200 G. Some of the authors suggest that these oscillations can be related to sunspot global eigen-modes as a whole. Efremov et al (2012a) have demonstrated that long-period ( = 10 -20 hours) oscillations of the magnetic field in bipolar groups are excited synchronously in the main and tail spots of a group.…”
Section: Long-period Oscillationsmentioning
confidence: 99%
“…Long-period magnetic field oscillations were detected from SOHO/MDI and ground-based data at Pulkovo Observatory by Nagovitsyna and Nagovitsyn (2002), Efremov et al (2007Efremov et al ( , 2009Efremov et al ( , 2012bEfremov et al ( , 2013, Kallunki and Riehokainen (2012), and with NoRH and SSRT instruments by AbramovMaximov et al (2013) and Bakunina et al (2013), finding periods of 30 -40, 70 -100, and 150 -200 and 800 -1300 minutes and amplitudes of about 200 G. Some of the authors suggest that these oscillations can be related to sunspot global eigen-modes as a whole. Efremov et al (2012a) have demonstrated that long-period ( = 10 -20 hours) oscillations of the magnetic field in bipolar groups are excited synchronously in the main and tail spots of a group.…”
Section: Long-period Oscillationsmentioning
confidence: 99%
“…Yuan et al (2011) revealed the long-period waves of about 29, 53, and 75 min in the lower corona. Recently, Bakunina et al (2013) and Chorley et al (2010) reported on the long-period oscillations in radio band in sunspot magnetospheres.…”
Section: Introductionmentioning
confidence: 99%
“…Only pixels where periods between 600 s (the lower limit for long-period oscillations defined by Bakunina et al 2013) and 1272 s (the maximum value allowed by the cone-of-influence) are present were selected as potential candidates for study here. Overall, 233 pixels (13.3 %) display signals above the 99 % confidence level in the studied temporal range, with each of these pixels being denoted by a coloured cross on Fig.…”
Section: Wavelet Analysismentioning
confidence: 99%
“…The majority of oscillations reported in both sunspots and pores have periodicities of around 3 to 5 minutes, however, several important examples of long-period oscillations (> 10 minutes; Bakunina et al 2013) have also been identified. Freij et al (2016) observed oscillations in the areas and intensities of two pores with periods of up to 35 minutes.…”
Section: Introductionmentioning
confidence: 99%